The Use of Genre Theory for Improving Writing Proficiency Skills in Explanations - Martínez Lirola, María (Íkala, Revista de Lenguaje y Cultura, 2015)
<!-- [if gte mso 9]> <![endif]--> The study reported in this paper focuses on the use of genre theory as an appropriate framework for English L2 writing in the subject English Language IV of the degree in English Studies. We compared 40 explanations written by students in this course at the University of Alicante (Spain) before and after they had studied different text types following genre theory. This study will show that using the theory of genre as a framework to teach academic writing helped students to improve their level of literacy through the study of text types and specific grammatical structures that appear in these texts. Findings suggest that exposing students to good models of different text types, paying special attention to explanations, and asking them to write texts based on these models, improves students’ texts from the grammatical and the textual points of view. <!-- [if gte mso 9]> Normal 0 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->